Uplink power control for multi-path channel estimation in massive multiple-input multiple-output systems - Jamal Amadid; Asma Khabba; Zakaria El Ouadi; Lahcen Sellak; Abdelmouttalib Bousrout; Abdelouhab Zeroual; Tole Sutikno (Institute of Advanced Engineering and Science, 2026)
Multi-path communication channels provide a realistic representation of transmitter-receiver communication in practical propagation environments. This work investigates uplink (UL) multi-path channel estimation (CE) in a massive multiple-input multiple-output (M-MIMO) multi-cell multi-user system, where each user communicates with its serving base station (BS) through a multi-path channel. The network operates using time-division duplex (TDD), exploiting channel reciprocity between the uplink and downlink. The impact of multi path propagation on CE is analyzed using two approaches: the ideal minimum mean square error (MMSE) estimator and a proposed simplified estimator. The MMSE estimator assumes prior knowledge of the large-scale fading (LSF) coefficients of interfering users, which is impractical in real systems. To overcome this limitation, a simplified estimator is proposed that does not require such information while achieving asymptotic performance close to that of the MMSE estimator. Realistic propagation scenarios are also considered, where channels may include either non-line-of-sight (NLoS) components or a combination of line-of-sight (LoS) and NLoS paths depending on the user’s distance from the BS. Furthermore, a heuristic power control strategy is introduced to mitigate pilot contamination, particularly for cell-edge users, thereby reducing inter-cell interference and improving overall system performance. Analytical and simulation results validate the proposed approach.